Cover. Issue 1 (23rd February 2023) - Noshad, David; Ukrainetz, Nicholas; King, John; Yanchuk, Alvin
Abstract : The cover image is based on the Original Article Epicuticular wax content of western white pine is involved in Cronartium ribicola resistance by David Noshad et al., https://doi.org/10.1111/efp.12793